Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes the major factors that may have contributed to the marked widening of the external current account imbalance in Greece since the mid-1990s, with the deficit reaching one of the highest levels (in relation to GDP) among advanced economies. The factors reviewed include developments in relative cost and other competitiveness indicators, business cycle asynchronization, and idiosyncratic supply shocks and immigration. Potential implications of euro area entry are discussed, in particular the impact of declining interest rates in the context of monetary union.